Thermoplastic Starch Composites With Titanium Dioxide and Vancomycin Antibiotic: Preparation, Morphology, Thermomechanical Properties, and Antimicrobial Susceptibility Testing - Ujcic, Aleksandra; Krejcikova, Sabina; Nevoralova, Martina; Zhigunov, Alexander; Dybal, Jiri; Krulis, Zdenek; Fulin, Petr; Nyc, Otakar; Slouf, Miroslav (Frontiers in Materials, 2020)
Biodegradable composites of thermoplastic starch (TPS), titanium dioxide particles (TiO2; average size 0.2 μm) and/or antibiotic (ATB; vancomycin) were prepared. For the preparation, we employed our recently developed two-step procedure, consisting of solution casting and melt mixing. The structure and properties of all samples was characterized thoroughly by microscopic, spectroscopic, diffraction, and rheological methods. It has been demonstrated that our two-step preparation procedure yields highly homogeneous TPS matrix with well dispersed TiO2 particles even for high filler concentrations (up to 20 %). The final TPS composites were sufficiently soft to be cut with a sharp blade at room temperature, the TPS matrix was fully biodegradable, the TiO2 filler was biocompatible, and the ATB could be released locally during the matrix degradation. Selected samples were tested for bacterial susceptibility using standard tube dilution test and disk diffusion test. The results proved that the ATB retained its bacteriostatic and bactericidal properties after the thermal processing of the composites. Therefore, the prepared TPS/TiO2/ATB composites represent a promising material for biomedical applications related to the local release of antibiotics.